Perception of Chilean Education Professionals on the Diagnosis and Treatment of Developmental Language Disorder - Vergara, Carla; Urrutia, Mabel; Domínguez, Alberto (Revista Chilena de Fonoaudiología, 2024)
Developmental Language Disorder (DLD) is increasingly prevalent in childhood. In this context, the perception of therapists and education professionals is crucial to improving clinical and educational practices related to its treatment. This qualitative phenomenographic study addresses the personal experiences, perceptions, and practices of therapists and education professionals in charge of treating DLD within educational settings in Chile through semi-structured interviews. The sample includes ten professionals with experience working in schools dedicated to language therapy and schools with Programa de Integracion Escolar (School Integration Program) in the south of the country. The content of the interviews was subject to thematic analysis, which yielded three central themes: the heterogeneity of DLD, perceptions of the experience of working with children, and therapeutic and educational interventions’ structure. This research highlights the diversity of approaches and challenges professionals face in treating DLD. The results reflect a need for consensus to improve the terminology, classification criteria, and assessments in this area, with limitations that point to future research that expands the sample and includes other Spanish-speaking contexts. This study has significant projections for updating interventions and standardizing assessment instruments for DLD.